AB0287 Efficacy of etanercept (etn) plus methotrexate (mtx) vs. disease-modifying anti-rheumatic drug (dmard) combinations with mtx in established rheumatoid arthritis (ra): duration of disease and disease severity vs. outcomes. (23rd January 2014) - Fleischmann, R.; Koenig, A. S.; Szumski, A.; Nab, H.; Marshall, L.; Bananis, E.
Abstract : Objectives: To assess the effect of disease duration (≤2 y vs. >2 y) and severity (moderate [mod] vs. severe [sev]) on treatment outcomes in subjects with RA receiving ETN+MTX or DMARDs+MTX. Methods: Data from subjects with mod-to-sev RA and an inadequate response to MTX were pooled from the APPEAL 1 (ETN 25 mg twice weekly+MTX or DMARD+MTX) and LatinRA 2 (ETN 50mg once weekly+MTX or DMARD+MTX) studies. 3 Endpoints included DAS28 (ESR) remission (<2.6) and LDA (<3.2), CDAI LDA (≤10) and remission (≤2.8), and a normal HAQ score of ≤0.5. Results: 478 subjects received ETN+MTX (≤2 y n=123, >2 y n=348; DAS28 3.2–5.1 [mod] n=45; DAS28 >5.1 [sev] n=431) and 245 subjects received DMARD+MTX (≤2 y n=60, >2 y n=180; DAS28 3.2–5.1 n=19; DAS28 >5.1 n=226). In the total population of each treatment group, ETN+MTX was more effective than DMARD+MTX (Table ). Patients with ≤2 y numerically had a better response than >2 y, as did patients with mod compared with sev for both treatment groups. ETN+MTX significantly outperformed DMARD + MTX in the >2 y and sev groups in all endpoints; in the ≤2 y group only DAS28 and CDAI LDA were superior as the ≤2 y and mod group had too few patients to detect a treatment difference. Within the treatment groups, significantly higher proportions of subjects with disease duration of ≤2 y vs. >2 y achieved HAQ ≤0.5 with ETN+MTX (P<0.05) and DAS28 and CDAI remission with DMARDs+MTX (P<0.05 for all). Higher proportions of subjects with mod vs. sev achieved DAS28/CDAI LDA and CDAI remission with ETN+MTX, and DAS28 LDA/remission, CDAI LDA, and HAQ ≤0.5 with DMARDs+MTX (P<0.01). Conclusions: Combination ETN+MTX was more effective than DMARDs+MTX in subjects with disease duration of >2 y and sev disease activity. Achievement of remission and optimal response was generally achieved in a higher number of subjects with shorter disease duration and mod disease activity. References: Kim HY et al. Int J Rheum Dis 2012;15:188-96. Machado D et al. PANLAR 2012: Poster. Fleischmann R, et al. Arthritis and Rheumatism 2012;64:S550. Acknowledgements: This study was sponsored by Pfizer Inc. Medical writing support was provided by Kim Brown of UBC Scientific Solutions and was funded by Pfizer Inc. Disclosure of Interest: R. Fleischmann Grant/research support from: Genentech Inc, Roche, Abbott, Amgen, UCB, Pfizer Inc, BMS, Lilly, Sanofi Aventis, Lexicon, MSD, Novartis, BiogenIdec, Astellas, Astra-Zeneca, Janssen, Consultant for: Roche, Abbott, Amgen, UCB, Pfizer, BMS, Lilly, Sanofi Aventis, Lexicon, Novartis, Astellas, Astra-Zeneca, Janssen, HGS, A. Koenig Employee of: Pfizer Inc., A. Szumski: None Declared, H. Nab Employee of: Pfizer Europe, L. Marshall Employee of: Pfizer Inc., E. Bananis Employee of: Pfizer Inc.